2000
DOI: 10.1002/1521-3951(200007)220:1<27::aid-pssb27>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Level Model for Intra-Well Exciton Migration in Zn1xCdxSe Quantum Wells

Abstract: In this work we present a simple two-level model, which can be employed to describe the migration of weakly localized excitons in quantum wells (QW). The migration of excitons is an intra-well process which can be readily observed in QWs which present thickness fluctuations of a few monolayers that extend over large area terraces (also called islands) with dimensions much larger than the Bohr radius of the exciton. This effect is experimentally observed as relative changes of the intensity of the spontaneous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Calculations were made for two structurally different Znl-xCdxSe QWs [2,6,7]. The parameters used in calculation are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations were made for two structurally different Znl-xCdxSe QWs [2,6,7]. The parameters used in calculation are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Bound excitons (BX) [3] and biexcitons (BB) [4,5] have been assigned to optical transitions in the PL spectra of ZnI _ 1 Cd, Se QWs. In previous papers we have analyzed in detail the mechanisms of exciton localization and exciton migration as a function of temperature for the case of two structurally different Zn -,Cd, Se QWs grown by molecular beam epitaxy (MBE) with different barrier materials [2,6,7]. Based on those studies we have made estimates of the relative total area of islands with different thickness, but that analysis does not give information about the area of individual islands [2].…”
Section: Introductionmentioning
confidence: 99%
“…We have observed a similar temperature behavior of the spectra lineshape in ZnCdSe QWs. [5], a detailed comparison of the experiment with the calculation will be published elsewhere.…”
Section: Exciton Populationmentioning
confidence: 99%
“…2 we can observe several components of the PL emission; as mentioned before, the peak around 2.5114 eV ͑that we will call P 1 ͒ is attributed to islands 50.4 Å thick, the peak around 2.504 eV ( P 2 ) could be associated to a larger QW or to a bound exciton, 7 we have demonstrated that the peak is due to transitions from a 2 monolayer larger island of the QW. 15 As we go from the UV ͑3250 Å͒ to the blue-green ͑4880 Å͒ excitation lines, it is quite evident a change in the relative intensities of these peaks. Figure 4͑a͒ shows the ratio of the integrated area of the PL peaks corresponding to those transitions.…”
Section: B Photoluminescence Enhancementmentioning
confidence: 99%
“…This effect is due to modification of exciton localization by resonant absorption and has been observed in other Zn 1Ϫx Cd x Se QWs. 9,15 …”
Section: B Photoluminescence Enhancementmentioning
confidence: 99%